A review of antibiotic resistance among Campylobacter species in human, animal, and water sources in South Africa: a One Health Approach. (20th December 2022) - Chibwe, Mary; Odume, Oghenekaro Nelson; Nnadozie, Chika Felicitas
Abstract: Campylobacter species are among the aetiological agents responsible for 400–500 million human diarrhoea cases per annum. The risk of dissemination of antibiotic-resistant Campylobacter species between humans, animals, and the environment is anticipated, given its transmissibility through these sources. The objective of this paper is to present a situation analysis that reports the current patterns and determinants of Campylobacter antibiotic resistance in South Africa. This review applies the One Health (OH) Approach to systematically review and collate the current antibiotic resistance status among Campylobacter spp. in South Africa. The highest level of resistance of Campylobacter in humans is to azithromycin (69.7%), whereas the lowest level of resistance of Campylobacter is to gatifloxacin (8.3%). In animals, high resistance to common antibiotics erythromycin (95.06%), clindamycin (95.68%), doxycycline (87.65%), erythromycin (90%), tetracycline (84.3%), streptomycin (88%), and ampicillin (73%) while 100% resistance of Campylobacter from water samples to tetracycline, imipenem, is recorded. Furthermore, resistance to clarithromycin (95%), azithromycin (92%), clindamycin (84.2%), doxycycline (80%), and ciprofloxacin (77.8%) is reported among Campylobacter spp. from water samples. The genetic similarity results suggest the movement of antibiotic-resistant Campylobacter spp. between humans and the environment. More research on antibiotic resistance among Campylobacter from other sources, outside clinical isolates, is recommended. HIGHLIGHTS: High antibiotic resistance among Campylobacter isolates from humans, animals, and water in South Africa is observed. There is an increased risk of waterborne antibiotic-resistant Campylobacter infections for communities that rely on the rivers for domestic and agricultural (irrigation) purposes. More investigations of antibiotic resistance in Campylobacter of aquatic environmental origin are emphasised. Graphical Abstract